A Novel Approach for People Counting and Tracking from Crowd Video - Sagun, M. Ayyuce Kizrak; Bolat, Bulent (IEEE, 2017)
Crowd analysis on video recordings is an important research area currently. In this work, a combined crowd density estimation method is presented to overcome this problem. To improve the accuracy of the system two different estimators run simultaneously and a blob is marked as a person only if both estimators mark it as person. One of the main problems in crowd density estimation is occlusion. To overcome this problem we tracked the trajectories of blobs by using a Kalman filter. The method was applied to three common benchmark data which are PETS2009, UCSD and Grand Central. The results confirm the proposed method's success.
Keywords: Crowd density; SIFT; complex wavelet transform; Optical flow; Kalman filtering; Video processing; Computer Science